Simulation of Galvanic Corrosion for Aluminum, Copper, Iron and Zinc at different pH and temperatures - Al-zubidy, Ekhlas A Salman (Al-Nahrain Journal of Science, 2013)
Simple model is proposed to describe galvanic corrosion process. Computer program COR was designed and written in visual basic language to simulate the galvanic corrosion reaction that proposed in the model. Input data metals parameters (aluminum, copper,iron, and zinc) and the environment parameters (pHand temperature) was used in the program designed COR and the results (The electrochemical parameters, corrosion rates, activation energies, and thermodynamic parameters)were calculated and discussed.Simulation computational results are compared with theoretical and experimental data, to ensure that the results of this model are corresponding to the results published in the literature. Both of which show the same characteristics of data distribution. The corrosion rates of iron were higher, followed by copper, zinc and finally aluminum.